“Can someone tell me what’s going on with my child?”: A qualitative study on parental health-seeking behavior for infant regulatory problems - Febe Hertveldt; Guido Van Hal; Edwin Wouters; Koen Ponnet; Binu Singh; Helena Van den Steene; Monica Dhar; Bea R.H. Van den Bergh; Hadewych Weyns; Sara De Bruyn (Archives of Public Health)
Abstract Background According to the principles of infant mental health care, young children’s gradual attainment of self-regulation is closely tied to co-regulation provided by the caregiver(s). Sometimes, these co- and self-regulatory processes are not seamless and regulatory problems (RP) can arise, which manifest themselves according to age and developmental stage of the child. Parents of children with RP often face prolonged periods of seeking specialized care and become entangled in a cycle of ineffective health-seeking behaviors. The present study aims to understand parental health-seeking behavior in response to their infant’s RP, and the missed opportunities therein, by retrospectively analyzing the healthcare journey of families. Methods Respondents were sampled in collaboration with child psychiatrists from two tertiary care infant mental health day clinics, using extreme case study sampling. Semi-structured interviews were conducted with 14 families (10 fathers and 15 mothers). The mean age of the infants at the time of admission was almost 11 months. The research interviews were qualitatively analyzed via reflexive thematic analysis in NVivo, within the design of a qualitative descriptive study. Results Four main themes are identified. (1) ‘The need for answers’ highlights the fact that parental concerns about what is normal infant behavior, and about possible underlying causes, are significant triggers for seeking (professional) help. (2) ‘The search for recognition and understanding’ identifies the profound impact on parents of being validated by their social network, but also by healthcare providers, in order to obtain timely referrals to specialized care. (3) ‘The lack of a broader approach’ discusses the importance of a holistic approach, which considers not only the physical but also the socio-emotional health of the infant, along with the well-being of parents. (4) ‘Lost in a healthcare maze’ emphasizes how parents feel abandoned by healthcare providers during their search for help. Conclusions The complex and fragmented nature of parents’ search for help often results in delayed referrals to specialized care. Parents believe that the care pathway for families with infants experiencing RP could be improved by addressing the identified missed opportunities.